Predictors and Recurrence Patterns After Radical Surgery in Ampulla of Vater Cancer: Comparative Analysis Between Early and Late Recurrence - Zhang, Zheng-Yun; Liu, Da-Wei; Hao, Di-Si; Zhou, Zun-Qiang (Frontiers in Surgery, 2022)
Objective: Tumor recurrence remains the main dilemma after surgical treatment of ampulla of Vater carcinoma. This study was designed to identify the prognostic factors and evaluate the recurrence patterns of ampulla of Vater cancer. Methods: A total of 286 patients who underwent surgical resection of ampulla of Vater cancer in two medical centers from January 2000 to October 2016 were collected. Data on clinicopathologic factors, survival rate, and recurrence patterns were retrospectively analyzed. Results: A total of 158 patients (55.2%) survived without evidence of recurrence (non-recurrence), whereas 65 (22.7%) and 63 patients (22.1%) suffered from recurrence of the disease within 12 months (early recurrence) and after 12 months (late recurrence), respectively. Early-recurrence patients exhibited a more advanced disease (advanced tumor stage, lymph node involvement, pancreas invasion, and late TNM stage) than late-recurrence patients. The first or primary location of cancer recurrence in 33 patients (25.8%) was locoregional. Metastasis developed in the liver in 30 patients (23.4%), peritoneum in 13 patients (10.2%), lungs in 10 patients (7.8%), and para-aortic or superior mesenteric artery lymph node in 10 patients (7.8%). Multiple metastases were observed in 26 patients (20.3%). Conclusion: The most common patterns of postoperative recurrence are locoregional and recurrent liver metastasis. The recurrence patterns with the worst prognosis are peritoneal and multiple metastases.